2021
DOI: 10.1093/jn/nxab301
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Plant-Based Dietary Patterns and Diabetes in Puerto Rican Adults

Abstract: Background Vegetarian-type dietary patterns have been associated with reducing the risk of developing diabetes and may function as an effective strategy for diabetes management. Objectives We aimed to examine the associations between adherence to plant-based diet indices and the risk of developing diabetes in the Boston Puerto Rican Health Study. Methods Puer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
7
1
Order By: Relevance
“…Chen et al, 2018;Laouali et al, 2021;A. Satija et al, 2016) Similar to type 2 diabetes, (Flores et al, 2021;Laouali et al, 2021;A. Satija et al, 2016) we found the association between the uPDI with obesity to be less apparent than has been demonstrated with cardiovascular disease.…”
Section: Findings In the Context Of Existing Literaturesupporting
confidence: 47%
“…Chen et al, 2018;Laouali et al, 2021;A. Satija et al, 2016) Similar to type 2 diabetes, (Flores et al, 2021;Laouali et al, 2021;A. Satija et al, 2016) we found the association between the uPDI with obesity to be less apparent than has been demonstrated with cardiovascular disease.…”
Section: Findings In the Context Of Existing Literaturesupporting
confidence: 47%
“…In addition, higher PDI values were associated with lower T2D risk in Chinese individuals in the SCHS, Henan Rural Cohort Study, and CHNS [ 14 , 18 , 24 ]. However, unlike our results, the Korean Genome and Epidemiology Study (KoGES) and Puerto Rico Cohort study demonstrated that PDI was not associated with T2D incidence [ 17 , 19 ]. These differences may be due to dietary habits, adjusted covariates, study inclusion criteria, and nondietary lifestyle risk factors.…”
Section: Discussioncontrasting
confidence: 99%
“…However, there are some gaps in previous studies on the relationship between a plant-based diet and T2D risk. First, studies on the correlation between PDI and T2D have presented inconclusive results, which are negative [ 5 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] or absent [ 19 , 20 , 21 ]. Second, the majority of research participants were from Western populations, whose dietary patterns and metabolic responses are different from those of Asian populations [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 Three plantbased diet indices (an overall plant-based diet index (PDI), a healthy PDI (hPDI), and a less-healthy (unhealthy) PDI (uPDI)) were created by Satija et al, 4 and they captured synergistic and graded intake of healthy (whole grains, fruits, vegetables, nuts, legumes, vegetable oils, and tea/coffee) and less healthy plantbased foods (fruit juices, refined grains, potatoes, sugar-sweetened beverages (SSBs), and sweets/desserts), as well as animal foods (dairy, animal fat, eggs, meat, fish or seafood, and miscellaneous animal-based foods). Many previous studies have examined the association between plant-based diet indices and chronic diseases such as cardiovascular diseases, 5,6 diabetes 4,7 and certain types of cancers [8][9][10] including lung cancer. 10 However, the results were inconsistent, and some studies demonstrated that high-quality plant based-diets were associated with a substantially lower risk of developing cardiovascular diseases, 5 diabetes, 4,7 breast cancer, 8,9 and digestive cancer, 10 while others showed no associations with cardiovascular diseases 6 and breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have examined the association between plant-based diet indices and chronic diseases such as cardiovascular diseases, 5,6 diabetes 4,7 and certain types of cancers [8][9][10] including lung cancer. 10 However, the results were inconsistent, and some studies demonstrated that high-quality plant based-diets were associated with a substantially lower risk of developing cardiovascular diseases, 5 diabetes, 4,7 breast cancer, 8,9 and digestive cancer, 10 while others showed no associations with cardiovascular diseases 6 and breast cancer. 10 For lung cancer, only one study reported a pro plant-based dietary score, consisting of healthy plant foods and animal foods, which was associated with decreased risks of lung cancer (HR t3 vs. t1, 0.47; 95% CI, 0.25-0.90; the P-value for trend, 0.02).…”
Section: Introductionmentioning
confidence: 99%